2019
DOI: 10.1149/2.0871913jes
|View full text |Cite
|
Sign up to set email alerts
|

Communication—Polyaniline Electrodeposition on Flexible ITO Substrates and the Effect of Curved Electrochemical Conditions

Abstract: Polyaniline (PANI) is a common electrically conducting polymer with numerous potential applications, including use in energy storage and electrochromic devices. In this communication, we describe the critical parameters for the deposition of PANI onto ITO-coated plastic, both under flat and curved conditions, and we explore the effects that the electrode curvature has on the electrochemical and electrochromic behavior of PANI. We found a simple water rinsing process after deposition was critical for good film … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…On the 60 Ω/□ films, electrodepositions could be reproducibly generated down to a normalized strain of approximately 0.10 (bending radius of 10 mm) based on quantification of the film coverage using ImageJ (Figure ). At higher strain, the deposition became less consistent, and at a bending radius of 5 mm or tighter, it was limited to the central portion of the electrode, in good agreement with our previous findings . Interestingly, at these higher strained conditions, the electrodeposition could be localized in different regions by changing the location of the electrical connection (Supporting Information Figure S2).…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…On the 60 Ω/□ films, electrodepositions could be reproducibly generated down to a normalized strain of approximately 0.10 (bending radius of 10 mm) based on quantification of the film coverage using ImageJ (Figure ). At higher strain, the deposition became less consistent, and at a bending radius of 5 mm or tighter, it was limited to the central portion of the electrode, in good agreement with our previous findings . Interestingly, at these higher strained conditions, the electrodeposition could be localized in different regions by changing the location of the electrical connection (Supporting Information Figure S2).…”
Section: Resultssupporting
confidence: 90%
“…Understanding the flexibility limits of ITO-PET electrodes for electrochemical applications is important for their practical deployment. This was highlighted in a recent communication from our research group that showed how the electrochemical deposition of polyaniline (PANI) and subsequent electrochemical behavior significantly changed below a bending radius of 7.5 mm . In the current study, we electrodeposited PANI onto commercially available ITO-PET substrates to elucidate the relationship between strain and electrochemical performance.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…An ITO-PET sheet was employed as a substrate with the aim to ensure some flexibility in the sensors. The sensors were obtained by electrodeposition of polyaniline following the procedure detailed in [68] by use of an electrolytic solution of 100 mM of aniline in 1 M of H 2 SO 4 . In order to deposit PANI, the potentiostatic deposition technique was employed, applying a potential of +2 V vs. SCE for 90 s, in a standard electrochemical system with three electrodes at room temperature.…”
Section: Electrode Fabricationmentioning
confidence: 99%
“…Beyond their hydrophilic and biocompatible properties, PEO-functionalized ITO nanocrystals could potentially be integrated into electrochromic devices, without the need for additional processing steps to remove the organic layer, since PEO is known to effectively conduct Li + . However, systematic studies on the influence of surface chemistry and polymer adsorption conditions on the morphology and properties of polymer-wrapped metal oxide nanocrystal thin films are needed toward the systematic engineering of these materials. Indeed, previous developments related to other hybrid polymer/metal oxide structures used as electrochromic materials, such as ITO surfaces functionalized with polythiophene, polypyrrole, or polyaniline, , have shown that the electrochromic response was intrinsically dependent on the polymer processing conditions and resulting composition/thickness.…”
Section: Introductionmentioning
confidence: 99%